Syed Hossein Nasr's Ecosufism: Re-examining the Relationship between God, Man and Nature to Solve the Environmental Crisis - Sadjali, Munir (MID Publisher International, 2024)
The phenomenon of environmental crisis in the modern era has occurred in all parts of the world, this crisis is caused by the loss of spiritual values and a paradigm shift from cosmocentric to anthropocentric, thus placing humans apart from the ecosystem environment. This research is a literature research, in this research there are two sources used, namely primary and secondary sources. Primary sources refer to the book Man and Nature: The Spiritual Crisis of Modern Man by Syed Hossein Nasr, while secondary sources include the works of people who have a connection with the problem to be studied The findings of this study show that Sufism in the modern era can contribute significantly in dealing with the environmental crisis. Eco-sufism is a new concept presented by Sufism scholars such as Syed Hossein Nasr with intelligent consideration of the environment and human welfare. The underlying premise of this awareness is that humans must understand and interact with their environment as a means of renewing their spiritual awareness. According to Nasr, the solution that must be understood in the development of ecosufism is the scope of ecosufism itself, namely knowing the relationship between God, humans and nature. Thus people will gain a fundamental understanding of the management of natural resources from an exploitative attitude towards nature through a study of Syed Hossein Nasr's ideas about eco-sufism. Consequently, nature becomes an integral part of human life.